Inteligencia lógica matemática y su contribución en el rendimiento académico a estudiantes de la escuela de educación básica “Francisco Robles”, cantón Babahoyo, Provincia los Ríos. - Valle Garzón, Tatiana Carolina (2016)
The mathematical logical intelligence inside the educational context, is an ability or gift that knowing it to impel and to develop allows the students to be manifested inside the process áulico like a skilled person to solve problems, be these operational, logical problems or of any nature or subject, besides developing an intellectual capacity of analysis and synthesis since that which allows him to stand out in the student range, its cognitive capacity and of learning he/she gives him a speed to analyze complicated situations and to find more logical and more feasible answers, making use of the learned contents and in an almost perfect synchronization of these with the experiences acquired in its interrelation with the means in which so much morals is unwrapped, physical and psychologically, that which is reflected in the academic yield. In the institution Francisco Oaks has not taken the due stocks that they allow that the discentes can acquire a knowledge that which favors, the stimulation of the mathematical logical intelligence for his good cognitive development, this has generated that the pupil is affected and present an index first floor of the academic yield because the tasks are accustomed to difficult tornarse for them.